Part III Singapore : the future project cargo hub of Southeast Asia - Heng, Yi Quan. (2013)
The emergence of Southeast Asia as one of the most important trade zones in the world is seen by many as the growth centre in the global economy. As the regional bloc continues to grow physically, the need for large scale infrastructure developments will present business opportunities for the project cargo industry.